Spontaneous Facial Mimicry is Modulated by Joint Attention and Autistic Traits. Issue 7 (7th October 2015) - Neufeld, Janina; Ioannou, Christina; Korb, Sebastian; Schilbach, Leonhard; Chakrabarti, Bhismadev
Abstract : Joint attention (JA) and spontaneous facial mimicry (SFM) are fundamental processes in social interactions, and they are closely related to empathic abilities. When tested independently, both of these processes have been usually observed to be atypical in individuals with autism spectrum conditions (ASC). However, it is not known how these processes interact with each other in relation to autistic traits. This study addresses this question by testing the impact of JA on SFM of happy faces using a truly interactive paradigm. Sixty‐two neurotypical participants engaged in gaze‐based social interaction with an anthropomorphic, gaze‐contingent virtual agent. The agent either established JA by initiating eye contact or looked away, before looking at an object and expressing happiness or disgust. Eye tracking was used to make the agent's gaze behavior and facial actions contingent to the participants' gaze. SFM of happy expressions was measured by Electromyography (EMG) recording over the Zygomaticus Major muscle. Results showed that JA augments SFM in individuals with low compared with high autistic traits. These findings are in line with reports of reduced impact of JA on action imitation in individuals with ASC. Moreover, they suggest that investigating atypical interactions between empathic processes, instead of testing these processes individually, might be crucial to understanding the nature of social deficits in autism. Autism Res 2016, 9: 781–789 . © 2015 The Authors Autism Research published by Wiley Periodicals, Inc. on behalf of International Society for Autism Research